Prompt Penetration Electric Fields and Ionospheric Effects of Major Geomagnetic Storms on Low Latitude Stations. - Talemwa, Gorretti (Kabale University, 2025)
This study investigated the characteristics and impacts of Prompt Penetration Electric Fields (PPEFs) on the ionosphere at low latitudes during major geomagnetic storms. The research explored the dynamics of the ionosphere by focusing on three key objectives: (i) classifying geomagnetic storms based on their intensity and nature, (ii) examining the condition of the ionosphere before, during, and after geomagnetic storms to understand temporal variations, and (iii) assessing the effects of PPEFs on the total electron current in the ionosphere at low-latitude stations. Using data collected from low-latitude observatories, the study analyzed variations in ionospheric parameters such as electron density and current systems. Findings contributed to understanding how geomagnetic disturbances influence ionospheric behavior, with implications for space weather prediction and the mitigation of disruptions to communication and navigation systems.